2016
DOI: 10.1101/055459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual transmission causes a marked increase in the incidence of Zika in women in Rio de Janeiro, Brazil

Abstract: The recent emergence of Zika in Brazil and its association with increased congenital malformation rates has raised concerns over its impact on the birth rates in the country. Using data on the incidence of Zika in 2015-2016 and dengue in 2013 and 2015-16 for the city of Rio de Janeiro (pop: 6.4 million), we document a massive increase of Zika in women compared to men. Even after correcting for the bias due to the systematic testing of pregnant women for Zika, there are 90% more registered cases per 100,000 wom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The interval between the onset of symptoms in the man and his partner has been observed to vary from 4 to 44 days [10]. Recently published data show a higher incidence of ZIKV infection in women of reproductive age in Brazil, suggesting a potential role for sexual transmission in the outbreak dynamic [11]. Knowledge on the maximum delay for possible sexual transmission from the time of infection, as well as knowledge of possible transmissions from asymptomatic infected individuals, are of real interest for public health in terms of establishing control measures, improving surveillance to detect the emergence of ZIKV in areas with no current circulation but where Aedes is established, and in terms of understanding the outbreak dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…The interval between the onset of symptoms in the man and his partner has been observed to vary from 4 to 44 days [10]. Recently published data show a higher incidence of ZIKV infection in women of reproductive age in Brazil, suggesting a potential role for sexual transmission in the outbreak dynamic [11]. Knowledge on the maximum delay for possible sexual transmission from the time of infection, as well as knowledge of possible transmissions from asymptomatic infected individuals, are of real interest for public health in terms of establishing control measures, improving surveillance to detect the emergence of ZIKV in areas with no current circulation but where Aedes is established, and in terms of understanding the outbreak dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the previous numbers can be considered as overestimates. On the other hand, indication of sexual transmission is increasing ( Coelho et al 2016 , Mansuy et al 2016 ) and preventive measures should be taken, as recommended by WHO. Although recent studies have shown that the reproductive number of Zika outbreak is higher than that of dengue in Rio de Janeiro ( Bastos et al 2016 ), these analyses correspond to its evolution during local summertime.…”
mentioning
confidence: 99%
“…However, experts caution that since women are more likely than men to visit a doctor, they’re also more likely to be tested 16 . Now that Zika has become notorious in Brazil, Marquez says it’s likely gone from being underreported to being overreported.…”
Section: Emerging Evidencementioning
confidence: 99%